2022
DOI: 10.1038/s41598-022-09908-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on the association between CD36 rs1761667 polymorphism and cardiometabolic risk factors in adults

Abstract: The cluster of differentiation 36 (CD36) is one of the main receptors implicated in the pathogenesis of the cardiovascular disease. This study aimed to assess the association between CD36 rs1761667 polymorphism and cardiometabolic risk factors including body mass index (BMI), waist circumference (WC), total cholesterol (TC), triglyceride, HDL-C, LDL-C, blood pressure and fasting blood glucose (FBG). PubMed, EMBASE, Scopus, web of science, and Google Scholar were searched up to December 2021. Subgroup and meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
(153 reference statements)
1
7
0
Order By: Relevance
“…In line with our results, a study on nondiabetic subjects reported no relationship between this polymorphism and the components of MetS in Caucasians [17]. This discrepancy in these results might be from several reasons, including different ethnicity, gene-environment and gene-gene interactions, clinical heterogeneity, and variation of the health status in different populations [18].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In line with our results, a study on nondiabetic subjects reported no relationship between this polymorphism and the components of MetS in Caucasians [17]. This discrepancy in these results might be from several reasons, including different ethnicity, gene-environment and gene-gene interactions, clinical heterogeneity, and variation of the health status in different populations [18].…”
Section: Discussionsupporting
confidence: 81%
“…A meta-analysis of studies reported a significant association between rs1761667 and triglyceride (TG) (allelic, recessive, and homozygous models), HDL-C, and fasting blood glucose (FBG) level (recessive genetic model). Furthermore, it has been reported that the A allele was associated with higher HDL-C and lower total cholesterol and low-density lipoprotein cholesterol levels in Asians [18]. Furthermore, several research studies provided evidence regarding the relationship of this polymorphism with hypertension, dyslipidemia, obesity, metabolic syndrome, type 2 diabetes mellitus, consumption of total fat, and fat orosensory perception [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies in findings might be due to the variations in the genotyping methods, ethnicity, health status, gene-environment or gene-gene interactions, and interactions of rs1761667 polymorphism with other variants in the CD36 gene. Another possible reason for these inconsistencies could be differences in the design of studies (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason for these inconsistencies could be differences in the design of studies (20) . Both deficiency and abnormally up-regulated CD36 lead to dyslipidaemia, metabolic disorders, inflammation and thrombosis (14) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation